Leakage detection techniques for oil and gas pipelines: State-of-the-art. (April 2020) - Lu, Hongfang; Iseley, Tom; Behbahani, Saleh; Fu, Lingdi
Abstract: The leakage of oil and gas pipelines may cause significant safety accidents and economic losses. In order to reduce the probability of pipeline failure, leak detection of pipelines is an effective measure. This paper introduces the existing detection methods that can be used in oil and gas pipelines, and analyzes their advantages, limitations, applicable occasions, and performance, so as to provide the reference for the selection of oil and gas pipeline detection technology in engineering. Moreover, this paper summarizes and classifies the existing standards for oil and gas pipeline leakage detection and analyzes the future development direction.